STUDI HADIS DI KALANGAN ORIENTALISME - Aan Supian (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
Orientalism was originally conceived as an ideology or thought  alliran undertaken by Western scholars to the development and  progress of East countries, both from the aspect of religion, language, culture,  history and  other  aspects. Later, some experts said that a study conducted by Western scholars of the East, primarily related to the Arab and  Islamic world. One of the studies in the field of Islam is the Hadith. Some  Orientalists much consern in Hadith studies, among others, Ignaz Goldziher and Joseph Schacht. Among the views Goldziher about  tradition  is that most  traditions  can  not be trusted  as a whole  as a source of teachings originating from the  Prophet. Most of the  material hadith  in the  collections of hadith  originating  from the  development of the religious, social and historical Islam is derived  from the characters in the first two centuries of tradition (century I and II H). It is similar, even more  extreme, Joseph Schacht argued  that the traditions  that were  collected in the book  of hadith  basically sourced from the Successors (formula  scholars centuries II and  III H), no one  hadist authentic sources of the Prophet, especially  the traditions  about  their law problem